Draft Genome Sequence of a Multidrug-Resistant Acinetobacter baumannii Strain from Chile - Opazo, Andrés (Genome Announc, 2015)
Acinetobacter baumannii strain Ab5 was isolated in the year 2007 in Chile, being one of the first multidrug-resistant (MDR) cases reported in the country. Here, we present the very first draft genome sequence of an MDR Chilean strain, which shows the presence of diverse resistance and acquired virulence genes.